USAGE OF INFORMATION TECHNOLOGIES IN THE PROCESS OF TEACHING FOREIGN LANGUAGES OF TECHNICAL UNIVERSITY STUDENTS - Aliyeva Begim-khanim Boyuk Aga (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the peculiarities of the use of multimedia presentations in the process of teaching a foreign language to students of technical universities. The educational process uses multimedia encyclopedias, tutors, tutorials, tests and individual assignments. However, in the educational process of higher education, the use of electronic presentations is the most acceptable way of using a computer that helps to competently organize the learning process, since the degree of assimilation of audiovisual information is very high.The interactivity of the presentation makes it the most popular form of communication visualization in life. Presentations serve not only to present knowledge when studying new material, presenting new information, but also to control them, consolidate what has been passed, work out educational skills and skills, repeat the practical application of the acquired knowledge, abilities, skills, generalization, systematization of knowledge, therefore, they successfully perform didactic functions.The basic requirements for the creation of multimedia presentations, their use and the principles of organizing this form of education are described. Presentations can support discussion. With the use of information technology, the very concept of education is currently changing.The article discusses new principles of a specific nature. allowing to form presentation competence necessary for various activities in the curriculum, productive plans and in real life, and in the future - the formation of the media culture of the future professional.